Bio-energy auditing, system productivity, energy efficiencies and economics of different direct-seeded basmati rice-based cropping systems and nutrient management options - Rakesh Kumar Verma; Yashbir Singh Shivay; Radha Prasanna; Prakash Chand Ghasal; Chiter Mal Parihar; Mukesh Choudhary; Raghavendra Madar (CABI Agriculture and Bioscience)
Abstract Background Diversification, intensification, new water and integrated nutrient management methods of rice-based cropping systems are being advocated as an alternative to the water-intensive nature of conventional rice cultivation in north-western India to address the issues of decline in the productivity, energy and nutritional scarcity and deteriorating soil fertility. Hence, the development of eco-friendly cropping systems with efficient nutrient management is essential for sustainable productivity. Material and methods The experiment was conducted with four cropping systems viz. direct-seeded basmati rice (DSBR)-wheat-fallow, DSBR-wheat-greengram, DSBR-cabbage-greengram and DSBR-cabbage-onion, being assigned to vertical strips; and 4 nutrient management strategies (MNS), viz. control, 100% RDF (recommended dose of fertilizers), 50% RDF + 25% RDN (recommended dose of nitrogen) through leaf compost + biofertilizers and 50% RDF + 25% RDN through vermicompost + biofertilizers assigned to horizontal strips. Results The highest system productivity (20.7 Mg/ha) was registered in DSBR-cabbage-onion and with a nutrient management strategy of 50% RDF + 25% RDN through vermicompost + biofertilizers (13.5 Mg/ha). The highest net energy (269.6 × 103 MJ/ha) was generated under DSBR-wheat-greengram. Among different NMS, the highest energy output efficiency was recorded under NS3 (0.20 × 103 MJ/ha/day). The CS2 had 20.4% and 20.2% higher total system protein yield and protein equivalent yield for adults than DSBR-wheat-fallow, respectively. Application of NS3 had the highest total system protein yield (89.7%) and protein equivalent yield for adults (92.6%) over the control (NS0). The maximum net return (5755 US$/ha) was obtained under CS4. Conclusion A cropping system involving DSBR-cabbage-onion and application of 50% RDF + 25% RDN through vermicompost + biofertilizers is identified as the most productive, energy efficient and profitable production system.